GEOCHEMICAL EVOLUTION OF THE ZADOI ALKALINE-ULTRAMAFIC MASSIF, CIS-SAYAN AREA, SOUTHERN SIBERIA - Rasskazov S.V.; Il'yasova A.M.; Konev A.A.; Yasnygina T.A.; Maslovskaya M.N.; Fefelov N.N.; Demonterova E.I.; Saranina E.V. (My University, 2007)
The unaltered magmatic rocks of the Zadoi Massif were analyzed for Sr isotopic composition and concentrations of major oxides and trace elements by ICP MS. The evolution of the massif involved four phases: (i) perovskite and ilmenite clinopyroxenites, (ii) ijolites, (iii) nepheline syenites, and (iv) carbonatites. The perovskite clinopyroxenites have anomalously high Ce/Pb (223–1132) and Pr/Sr × 1000 (70–360) ratios at a low initial Sr isotopic ratio (87Sr/86Sr)0 = 0.70247–0.70285. The ilmenite clinopyroxenites have Ce/Pb and Pr/Sr × 1000 ratios approaching those in basalts of oceanic islands (OIB) (decreasing to 39 and 30, respectively) at a simultaneous increase in the (87Sr/86Sr)0 ratios (0.7030–0.7036). The ijolites and nepheline syenites have patterns of incompatible trace elements similar to those in OIB and the highest (87Sr/86Sr)0 ratios (0.70346–0.70414). The carbonatites are complementarily enriched in incompatible elements of the nepheline syenites and have (87Sr/86Sr)0 = 0.7029–0.7034, which is comparable with the range of analogous ratios for the ilmenite clinopyroxenites. Our geochemical data indicate that the carbonatites were formed as an immiscible liquid or fluid, which separated from the ijolite-nepheline syenite melt during its interaction with the source material of the perovskite and ilmenite clinopyroxenites.